Effects of equivalent diameter on vertical PMMA combustion in natural convection environment. (29th August 2020) - Gou, Fu‐Hai; Xiao, Hua‐Hua; Jiang, Lin; Li, Mi; Lu, Wei; Zhang, Man‐Man; Sun, Jin‐Hua
Summary: A series of combustion experiments of polymethyl methacrylate (PMMA) plates with two shapes, three thicknesses, and different sizes was performed to investigate the effects of equivalent diameter on combustion characteristics of vertical PMMA in a natural convection environment. Two digital video cameras were used to record the burning process. The temporal variation of mass was recorded by an electronic balance. The influence of equivalent diameter on mass loss rate and flame height was then analyzed theoretically. Convection and radiation heat transfer were calculated and modeled in the theoretical analysis and compared to experiment. The result shows that the theoretical prediction of mass loss rate for each equivalent diameter is in good agreement with the experimental measurements. In addition, the relationship between flame height and heat release rate was analyzed using dimensionless analysis method. It was found that the flame height for vertical PMMA burning in a nature convection environment is dominated by heat release rate and equivalent diameter.